An efficient method for selective image encryption using wavelet transform for secure and fast communication - et. al., Ravikumar.K, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we suggest a new formulation of selective partial encryption based on the Discrete Wavelet Transform (DWT) in order to verify an optimal and assured transmission and storage of images. This approach is faster since it permits a very important gain in the encryption-decryption processing time and more efficient because it allows to get an encrypted image.